Composite end points to assess delay of disability progression by MS treatments. (October 2014) - Zhang, J; Waubant, E; Cutter, G; Wolinsky, JS; Leppert, D
Background: The Expanded Disability Status Scale (EDSS) has low sensitivity and reliability for detecting sustained disability progression (SDP) in multiple sclerosis (MS) trials. Objective: This study evaluated composite disability end points as alternatives to EDSS alone. Methods: SDP rates were determined using 96-week data from the Olympus trial (rituximab in patients with primary progressive MS). SDP was analyzed using composite disability end points: SDP in EDSS, timed 25-foot walk test (T25FWT), or 9-hole peg test (9HPT) (composite A); SDP in T25FWT or 9HPT (composite B); SDP in EDSS and (T25FWT or 9HPT) (composite C); and SDP in any two (EDSS, T25FWT, and 9HPT) (composite D). Results: Overall agreements between EDSS and other disability measures in defining SDP were 66%−73%. Composite A showed similar treatment effect estimate versus EDSS alone with much higher SDP rates. Composite B, C, and D all showed larger treatment effect estimate with different or similar SDP rates versus EDSS alone. Using composite A (24-week confirmation only), B, C, or D could reduce sample sizes needed for MS trials. Conclusion: Composite end points including multiple accepted disability measures could be superior to EDSS alone in analyzing disability progression and should be considered in future MS trials.